Pengaruh Kualitas Pelayanan Publik Terpadu dan Budaya Kerja terhadap Keputusan Masyarakat dalam Memanfaatkan Layanan Pemerintah Desa : Studi Pada Desa Kaladawa, Kecamatan Talang - Taslikhin Taslikhin (Universitas 45 Surabaya, 2025)
This study aims to analyze the influence of integrated public service quality and work culture of village officials on community decisions to utilize government services. The research was conducted in Kaladawa Village, Talang District, using a quantitative approach with descriptive and verificative methods. Data were collected through questionnaires, interviews, and observations involving 120 respondents who are users of village public services. The results indicate that both public service quality and work culture significantly affect community decisions. High-quality services characterized by speed, accuracy, and transparency enhance public satisfaction and trust in village governance. Meanwhile, a positive work culture—comprising discipline, responsibility, and professionalism—creates a supportive and service-oriented environment. Simultaneously, these two factors explain 67% of the variation in community decisions to use government services. The findings emphasize that improving public service quality should be accompanied by strengthening the work culture of village officials and implementing an integrated digital service system to ensure efficiency, transparency, and sustainability in village-level governance.